2021
DOI: 10.3390/sym13061051
|View full text |Cite
|
Sign up to set email alerts
|

A Damage Model to Trabecular Bone and Similar Materials: Residual Resource, Effective Elasticity Modulus, and Effective Stress under Uniaxial Compression

Abstract: Experimental research of bone strength remains costly and limited for ethical and technical reasons. Therefore, to predict the mechanical state of bone tissue, as well as similar materials, it is desirable to use computer technology and mathematical modeling. Yet, bone tissue as a bio-mechanical object with a hierarchical structure is difficult to analyze for strength and rigidity; therefore, empirical models are often used, the disadvantage of which is their limited application scope. The use of new analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…Remark 1: Note that Equation ( 12) was justified without postulating the law of damage evolution at the development start. Nevertheless, using the logic of fracture mechanics, a model of damage accumulation of quasi-brittle materials under uniaxial compression was substantiated, in which the final Equation ( 12) corresponds to the Weibull distribution law, which is confirmed by the equivalence of Equations ( 5) [22] and ( 12) [8] under condition (13).…”
Section: Example Of the Equivalence Of Two Approaches To Damage Determinationmentioning
confidence: 90%
See 4 more Smart Citations
“…Remark 1: Note that Equation ( 12) was justified without postulating the law of damage evolution at the development start. Nevertheless, using the logic of fracture mechanics, a model of damage accumulation of quasi-brittle materials under uniaxial compression was substantiated, in which the final Equation ( 12) corresponds to the Weibull distribution law, which is confirmed by the equivalence of Equations ( 5) [22] and ( 12) [8] under condition (13).…”
Section: Example Of the Equivalence Of Two Approaches To Damage Determinationmentioning
confidence: 90%
“…Using a different approach [8], it can be shown that for uniaxial compression, an analog of equation ( 5) can be obtained based on the assumption that the change in the effective area (d A) of the sample with the initial height H 0 and the initial cross-sectional area A 0 is proportional to the change in the elastic potential energy if the strain increases from ε to (ε + dε). In this case, the height of the sample varies from εH 0 to (ε + dε)H 0 .…”
Section: Example Of the Equivalence Of Two Approaches To Damage Determinationmentioning
confidence: 99%
See 3 more Smart Citations